Radio-loud flares from microquasars and radio-loudness of quasars - Nipoti, C; Blundell, K; Binney, J (2005)
The low-frequency power spectra of the X-ray and radio emission from four microquasars suggest that two distinct modes of energy output are at work: (i) the `coupled' mode in which the X-ray and radio luminosities are closely coupled and vary only weakly, and (ii) the `flaring' mode, which dramatically boosts the radio luminosity but makes no impact on the X-ray luminosity. The systems are in the flaring mode only a few percent of the time. However, flares completely dominate the power spectrum of radio emission, with the consequence that sources in which the flaring mode occurs, such as GRS 1915+105 and Cyg X-3, have radio power spectra that lie more than an order of magnitude above the corresponding X-ray power spectra. Of the four microquasars for which we have examined data, in only one, Cyg X-1, is the flaring mode seemingly inactive. While Cyg X-1 is a black-hole candidate, one of the three flaring sources, Sco X-1, is a neutron star. Consequently, it is likely that both modes are driven by the accretion disk rather than black-hole spin. Radio imaging strongly suggests that the flaring mode involves relativistic jets. A typical microquasar is in the flaring mode a few percent of the time, which is similar to the fraction of quasars that are radio loud. Thus there may be no essential difference between radio-loud and radio-quiet quasars; radio loudness may simply be a function of the epoch at which the source is observed.